2007
DOI: 10.1074/jbc.m700729200
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Homeodomain Fingers of Fission Yeast Msc1 Exhibit E3 Ubiquitin Ligase Activity

Abstract: The DNA damage checkpoint pathway governs how cells regulate cell cycle progression in response to DNA damage. A screen for suppressors of a fission yeast chk1 mutant defective in the checkpoint pathway identified a novel Schizosaccharomyces pombe protein, Msc1. Msc1 contains 3 plant homeodomain (PHD) finger motifs, characteristically defined by a C 4 HC 3 consensus similar to RING finger domains. PHD finger domains in viral proteins and in the cellular protein kinase MEKK1 (mitogen-activated protein kinase/ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 45 publications
(57 reference statements)
1
45
0
Order By: Relevance
“…However, it is still unclear whether MLL5 can modify p53 upon interaction, or MLL5 merely serves as a chromatin-anchored adapter for a larger protein complex that negatively regulates p53. Better characterization of the function of conserved domains on MLL5, such as the PHD zinc finger (Scheel and Hofmann, 2003;Dul and Walworth, 2007;Kim and Buratowski, 2009) and SET domain (Berger, 2002), will be useful to understand the nature of the negative regulation of p53 by MLL5 in more details.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether MLL5 can modify p53 upon interaction, or MLL5 merely serves as a chromatin-anchored adapter for a larger protein complex that negatively regulates p53. Better characterization of the function of conserved domains on MLL5, such as the PHD zinc finger (Scheel and Hofmann, 2003;Dul and Walworth, 2007;Kim and Buratowski, 2009) and SET domain (Berger, 2002), will be useful to understand the nature of the negative regulation of p53 by MLL5 in more details.…”
Section: Discussionmentioning
confidence: 99%
“…PHD domains were shown to bind different methylated lysines on the histone tail of H3 functioning as reader domains (7). Due to the high similarity to RING domains which are well known E3 ligase domains, the PHD domains were recently also analyzed for E3 ligase function (7,8). Fbox domains function most likely as an anchor between a target protein and an E3 ubiquitin ligase (9).…”
mentioning
confidence: 99%
“…Additionally, while the three PHD domains of Msc1 suggest that it may behave as a reader of H3 lysine methyl marks, we were unable to detect binding of the Msc1 PHD domains to histone proteins (Dul and Walworth 2007) or methyl-modified histone peptides (C. T. Bernard and N. C. Walworth, unpublished data). We could, however, demonstrate association of Msc1 with the ubiquitin-conjugating enzyme Rhp6 and found that the PHD domains of Msc1 possess E3 ubiquitin protein ligase activity, a property shared with PHD domains of several other proteins (Dul and Walworth 2007).…”
Section: Discussionmentioning
confidence: 75%
“…A role for Msc1 in chromosome segregation has become apparent as a result of both gain-and loss-of-function genetic interactions with various centromere and kinetochore mutants (Ahmed et al 2004(Ahmed et al , 2007Dul and Walworth 2007;Qiu et al 2010). A recent study suggests a role for a Msc1-mediated pathway in establishing neocentromeres in fission yeast (Ogiyama et al 2013).…”
Section: Codependent Function Of Msc1 In Chromosome Segregationmentioning
confidence: 99%
See 1 more Smart Citation